Development of methods for separation and determination of Pb, fractionation and speciation of As from waters using cellulose-based adsorbents - Fuentes, Dairon Pérez (2023)
The presence of potentially toxic elements, particularly lead and arsenic, in natural and drinking waters is of concern due to their widespread occurrence and harmful effects on human health. Therefore, developing materials and methods for removing, separating, and preconcentrating these elements is essential to mitigate contamination and for analytical purposes. Thus, the objective of the project was to develop methods for separation and determination of lead and fractionation and speciation of organic and inorganic species of arsenic in different water samples using cellulose-based adsorbent and detection by inductively coupled optical emission spectrometry (ICP OES) and graphite furnace atomic absorption spectroscopy (GF AAS). For the separation of lead from water, microcrystalline cellulose beads were prepared in 2 mol L-1 HNO3 as a coagulant medium, being named b-HNO3. The Pb(II) adsorption data fit to the Langmuir model, with a maximum adsorption capacity of 108 mg g-1. The b-HNO3 were characterized by SEM, FTIR, XPS, and elemental analysis, and the adsorption performance was evaluated by different methods such as zero charge point and adsorption isotherm. The methodology developed for separating Pb(II) was made in columns packed with b-HNO3. The adsorption efficiency depended on the pH between 6- 8 and flow rate of 0.5 mL min-1 of solution flowing through the column, making it possible to reuse the column for several separation cycles, with effective Pb(II) desorption with 2 mol L-1 of HCl. Applying the optimized conditions for separating Pb(II) from tap water, dam water, and high salinity water, recoveries ranging from 94% to 102% were obtained. Microcrystalline cellulose modified with glycidyl trimethylammonium chloride (MCC-GTA) was used as adsorbent for the fractionation and speciation of arsenic. Elemental analysis confirmed the incorporation of quaternary ammonium groups in the cellulose chain. Optimization studies demonstrated that MCC-GTA exhibited high affinity for As(V) at pH 6-7, with negligible adsorption of As(III), none of AsB, and moderate adsorption for MMAs and DMAs species, with percentages ranging from 30 to 50%, respectively. The adsorption process of As(V) was instantaneous and was not affected by the adsorbent mass. In this investigation, the studies were done in batch mode. The oxidation of As(III) to As(V) with sodium hypochlorite (NaClO) was one of the strategies for speciation, which did not affect the behavior of adsorption in MCC-GTA. Pre-concentration analysis and inorganic arsenic (iAs) speciation were performed in river water samples using batch MCC-GTA. The results showed that speciation of As(III) and As(V) was possible, with recoveries ranging from 93% to 109% for As(III) and 96% to 103% for As(V). Overall, the results demonstrated the efficiency of these materials, from natural sources, for separation of Pb(II) and speciation of As(III) from As(V) applied in natural water samples.